2018
DOI: 10.1038/s41467-018-04362-x
|View full text |Cite|
|
Sign up to set email alerts
|

Study of 300,486 individuals identifies 148 independent genetic loci influencing general cognitive function

Abstract: General cognitive function is a prominent and relatively stable human trait that is associated with many important life outcomes. We combine cognitive and genetic data from the CHARGE and COGENT consortia, and UK Biobank (total N = 300,486; age 16–102) and find 148 genome-wide significant independent loci (P < 5 × 10−8) associated with general cognitive function. Within the novel genetic loci are variants associated with neurodegenerative and neurodevelopmental disorders, physical and psychiatric illnesses, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
551
7
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 577 publications
(612 citation statements)
references
References 87 publications
31
551
7
10
Order By: Relevance
“…Interestingly, the RBL2 locus has been associated with intelligence and cognitive function further strengthening its role in brain development . Our findings establish RBL2 as a candidate gene for an autosomal recessive neurodevelopmental disorder with intellectual disability, stereotypies and dysmorphic features adding variants with a monogenic effect to the allelic series.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Interestingly, the RBL2 locus has been associated with intelligence and cognitive function further strengthening its role in brain development . Our findings establish RBL2 as a candidate gene for an autosomal recessive neurodevelopmental disorder with intellectual disability, stereotypies and dysmorphic features adding variants with a monogenic effect to the allelic series.…”
Section: Discussionsupporting
confidence: 51%
“…Genome‐wide association studies (GWAS) have identified polymorphisms in the RBL2 locus to be associated with intelligence and educational attainment, but the gene has not been described in a monogenic context to date.…”
Section: Introductionmentioning
confidence: 99%
“…For genome‐wide significant findings from published GWAS of general cognitive function (Davies et al, ), cognitive performance (Lee et al, ), and intelligence (Savage et al, ), the observed fractions of same‐direction tests observed in our analyses of EA and AA participants were significantly greater than expected by chance (i.e., 50%). These results are displayed in Table .…”
Section: Resultssupporting
confidence: 41%
“…By comparison, in the COGENT study, polygenic risk analyses suggested correlations between cognitive performance and educational performance, whereas in our GNOVA analyses of the UK Biobank data, our results were correlated with other cognitive impairments in the general population and occupations associated with reduced educational attainment. Previous GNOVA analyses of the COGENT study results suggested correlations of the genomics of global cognition with SZ and BP (Davies et al, ).…”
Section: Discussionmentioning
confidence: 81%
“…As an additional analysis, we tested whether rs2526377 is connected to cognitive functioning before the clinical manifestations of AD so that the variant can be used as early marker of disease. To this end, we examined the association of rs2526377 with cognitive ability and educational attainment using the publicly available GWAS data (Davies et al, ; Okbay et al, ). The SNP minor allele (G) was positively associated with cognitive function ( p = .046; β = 0.011) and educational attainment ( p = .005; β = 0.01), which is consistent with the protective effect of the G allele for AD risk.…”
Section: Resultsmentioning
confidence: 99%